The effects of different molecular weight chondroitin-4-sulfates in chondrocyte pellet culture - Yang, Shu-Rui (Cytotechnology, 2014)
For this study, we cultured chondrocyte pellets in Dulbecco’s modified Eagle’s medium plus a 2 % fetal bovine serum medium, and treated them with 2- to 8-mer oligosaccharides of chondroitin sulfate A to examine the effects of these oligosaccharides on the differentiation and protection of chondrocytes. We found low-molecular-weight CSAs to increase the ratio of the gene expression levels of collagen II/collagen I of chondrocytes from the first day up to 14 days after culture compared with those under a CSA-free medium. Moreover, low-molecular-weight CSAs inhibited the expression of matrix metalloproteinases and peptidases, and stimulated an endogenous tissue inhibitor of metalloproteinases. The dp-8 (8-mer) CSA yielded the most effective response among promoting collagen type II protein secretions compared with other groups. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10616-014-9788-y) contains supplementary material, which is available to authorized users.